Src-dependent tyrosine phosphorylation of non-muscle myosin heavy chain-IIA restricts Listeria monocytogenes cellular infection. - Almeida, MT (2015)
Bacterial pathogens often interfere with host tyrosine phosphorylation cascades to control host responses and cause infection. Given the role of tyrosine phosphorylation events in different human infections and our previous results showing the activation of the tyrosine kinase Src upon incubation of cells with Listeria monocytogenes, we searched for novel host proteins undergoing tyrosine phosphorylation upon L. monocytogenes infection. We identify the heavy chain of the non-muscle myosin IIA (NMHC-IIA) as being phosphorylated in a specific tyrosine residue in response to L. monocytogenes infection. We characterize this novel post-translational modification event and show that, upon L. monocytogenes infection, Src phosphorylates NMHC-IIA in a previously uncharacterized tyrosine residue (Tyr-158) located in its motor domain near the ATP-binding site. In addition, we found that other intracellular and extracellular bacterial pathogens trigger NMHC-IIA tyrosine phosphorylation. We demonstrate that NMHC-IIA limits intracellular levels of L. monocytogenes, and this is dependent on the phosphorylation of Tyr-158. Our data suggest a novel mechanism of regulation of NMHC-IIA activity relying on the phosphorylation of Tyr-158 by Src.